The Role Psychological Capital to Employee Job Satisfaction in a Private Company: A Study at PT. S: Peran Psychological Capital terhadap Kepuasan Kerja Karyawan Swasta di PT. S - Karlina; Annisa Rizkiayu Leofianti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
In an increasingly dynamic work environment, private companies face challenges in maintaining employee job satisfaction, affecting productivity and organizational sustainability. This study aimed to examine the effect of Psychological Capital (PsyCap) on job satisfaction. A quantitative approach with purposive sampling was employed, and data were analyzed using a Generalized Linear Model (GLM). The results indicated that PsyCap significantly influenced job satisfaction (Wald χ² = 365.035, p < 0.001) and explained 36.5% of the variance in job satisfaction. These findings highlight the importance of developing PsyCap to enhance employee job satisfaction and performance.